2003
DOI: 10.1590/s0004-27492003000700005
|View full text |Cite
|
Sign up to set email alerts
|

Alterações oculares na hanseníase, observadas em pacientes ambulatoriais do serviço de referência da cidade de Rio Branco, Acre - Brasil

Abstract: Alterações oculares na hanseníase, observadas em pacientes ambulatoriais do serviço de referência da cidade de Rio Branco, Acre -Brasil Objetivo: Determinar a prevalência das alterações oculares em pacientes de hanseníase ativa ou inativa, acompanhados em serviço de referência. Métodos: O estudo transversal constou de exame ocular e levantamento de dados demográficos e clínico-epidemiológicos, em serviço de referên-cia da cidade de Rio Branco (Acre), no período de outubro de 2001 a abril de 2002. Resultados: F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 13 publications
(17 reference statements)
1
9
1
9
Order By: Relevance
“…Regarding gender, other works observed predominance of males among affected population, differing of the data found in this study, since there was no statistically significant difference in this variable (10)(11) . …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding gender, other works observed predominance of males among affected population, differing of the data found in this study, since there was no statistically significant difference in this variable (10)(11) . …”
Section: Discussioncontrasting
confidence: 99%
“…In another study, Lepromatous leprosy was also the most frequent and the Indeterminate the less frequent (10) .…”
Section: Discussionmentioning
confidence: 88%
“…However, Moreno et al 28 found that an age of 40 years and older was a determinant in the occurrence of alterations in the eyes of leprosy patients (p<0.003). Julio et al 29 found that the male gender and an age of 33-54 years was associated with alterations in the nose.…”
Section: Discussionmentioning
confidence: 97%
“…As alterações dos anexos oculares são as mais freqüentes, sendo a madarose de supercílios encontrada em 40%, a de cílios em 33% e o lagoftalmo em 10% 1 dos pacientes com a forma virchowiana da doença 26 .…”
Section: -Discussãounclassified
“…As lesões no segmento posterior são pouco freqüentes e provocam pouca incapacidade visual quando comparadas às do segmento anterior. Vários autores descrevem lesões sugestivas da doença no segmento posterior 26,27 , inclusive com o relato de encontro do bacilo nessas áreas 28 . Alterações irianas na hanseníase acometem 7,2% dos pacientes e não são associadas à diminuição da visão 1,6,10 .…”
Section: -Discussãounclassified